The non-linear association between ascending aorta diameter and risk of 12-month mortality in Chinese patients with heart failure: A retrospective cohort study - Chen, Jin; Huang, Yuan-Lei; Huang, Hui; Zheng, Tao; Cong, Guang-Zhi (Frontiers in Cardiovascular Medicine, 2022)
Background: There is no definite evidence of the association between ascending aorta diameter (AoD) and the mortality risk of heart failure (HF). Therefore, the retrospective cohort study was conducted to examine whether the AoD is associated with 12-month mortality in Chinese HF patients. METHODS: We retrospectively collected 575 Chinese patients with HF from January 2017 to March 2020. The association was detected between AoD and 12-month all-cause mortality. Covariates included data on demographics, drug use, clinical features, recognized markers of HF, and comorbidities. Binary logistic regression and two-piecewise linear models were used to analyze independent associations of AoD with the risk of 12-month mortality. RESULTS: Our results suggest that the association between AoD and the risk of 12-month mortality was nonlinear. In the AoD range of 23 to 37, the AoD was not associated with the risk of mortality (Odds ratio (OR) 0.88, 95% confidence interval [CI], 0.76 to 1.02). Conversely, for every 1 mm increase in AoD, the risk of 12-month all-cause mortality increased by approximately 46% (Odds ratio 1.46, 95%CI, 1.04-2.06) in the AoD range of 37 to 49. CONCLUSION: for Chinese HF patients, AoD greater than 37 mm is a dangerous threshold. Because above this threshold, for every 1 mm increase in AoD, the 12-month risk of all-cause mortality increased by 46%